Identities, borders and gender violence: A critical debate in the works of four south american anthropologists - Guizardi, Menara (Universidad Católica del Norte, Instituto de Investigaciones Arqueológicas y Museo, 2021)
The article derives from a review of the state of the art on identities, gender and borders that recovers the post-Marxist anthropological critic of four South American authors. I will start with the debate of Darcy Ribeiro and Cardoso de Oliveira about identities, continuing with Grimson’s discussions on borders and identifications in South America, and I will reach Segato, in her arguments about the elementary structures of gender violence. In the final section, I return and synthesize the central aspects of the critical turns discussed throughout the text, and I will establish some approximations for new analytical proposals.